THE EFFECT OF USING VIDEO SONGS IN THE TEACHING OF ENGLISH VOCABULARY ON THE STUDENTS` LISTENING SKILL AT SMAN 1 KUANTAN HILIR SEBERANG - Irmawita, Dela; Masyhur, Masyhur; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The aim of this research was to find out whether there is significant effect of using video songs in the teaching of English vocabulary on the students` listening skill. This research was conducted at SMAN 1 Kuantan Hilir Seberang. It was applied by using one-group pre test-post test design. This is a pre-experimental research. The instruments were tests which consisted of listening and vocabulary. The researcher used 21 students as the sample. This research selected by used quantitative data and the instrument used to collect the data is a listening video song. The tests consisted of 25 items. The test was used to get data about students` ability in listening skill and their vocabulary mastery. In order to know the difference between the pre-test and the post-test and to analyze the hypothesis, t-test formula was used. It is found that, the mean score of pre-test and post-test is 68.19 and 73.90. In other words, the mean score of post-test is higher than the mean score of pre-test. The result also showed that the value of t-test (4.094) is higher than t-table (2.086) at the significance level 5%. It means that Alternative Hypothesis (Ha) is accepted and Null Hypothesis (Ho) is rejected. It means that the vocabulary mastery of the students in listening skill was significant.Key Words: Effect, Video Song, Vocabulary Mastery, Listening Skill.